Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1934578x19850046
|View full text |Cite
|
Sign up to set email alerts
|

New Acetophenone and Cardanol Derivatives From Knema pachycarpa

Abstract: Two new acetophenone derivatives named knepachycarpanone A (1) and knepachycarpanone B (2) together with a new cardanol derivative named knepachycarpanol C (3) were isolated from the EtOAc extract of Knema pachycarpa stems. Their chemical structures were established on the basis of spectral evidences. Compounds 1 and 2 exhibited moderate cytotoxicity against Hela cancer cell line with IC50 values of 26.92 ± 1.46 and 30.20 ± 1.97 μM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…Figure S33 shows the significant effect of the cytotoxic compounds 2 and 4 on the activation of caspase 3/7, which is essential in the induction and execution of apoptosis [ 41 ]. Taken together, our results are confirming the previously reported bioactivities of acetophenones [ 40 , 42 , 43 , 44 ]. Moreover, we also found that acetophenone derivatives containing prenyl substituents show particularly higher cytotoxic activities compared to other compounds not bearing such structure elements.…”
Section: Resultssupporting
confidence: 93%
“…Figure S33 shows the significant effect of the cytotoxic compounds 2 and 4 on the activation of caspase 3/7, which is essential in the induction and execution of apoptosis [ 41 ]. Taken together, our results are confirming the previously reported bioactivities of acetophenones [ 40 , 42 , 43 , 44 ]. Moreover, we also found that acetophenone derivatives containing prenyl substituents show particularly higher cytotoxic activities compared to other compounds not bearing such structure elements.…”
Section: Resultssupporting
confidence: 93%
“…Chemical investigation of the ethyl acetate extract of K. pachycarpa leaves led to the isolation of seven phenolic compounds including six flavonoids 5,7,3′-trihydroxy-5′-methoxy isoflavone (1), luteolin (2),(-)-narigenin (3), (+)-catechin (4), isoquercetrin (5), nicotiflorin (6) and a biphenyl compound 3,3',4,4'-tetrahydroxybiphenyl (7). Compounds 3 and 6-7 were isolated from Knema genus for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Plant Knema pachycarpa de Wilde, that is called "Mau cho trai day", is a native tree in Viet Nam and only few chemical studies of this Knema species have been reported by our group [5][6][7]. In our biological activity screening of Vietnamese plants, the MeOH extract of leaves of K. pachycarpa showed cytotoxic activity against KB cell line with IC 50 of 78.21 ± 4.35 g/mL.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[1,[3][4][5][6] Knema pachycarpa de Wilde "Mau cho trai day" is a native tree in Vietnam and only few chemical studies of this Knema species have been reported. In the continuation of our study on Knema species, [7][8][9][10] the chemical constituents of Knema pachycarpa leaves were investigated. Ten compounds were isolated and elucidated as (7''R, 8''R)-hydnocarpin D (1), (7''R, 8''R)-hydnocarpin (2), sinaicitin (3), (-)-globulol (4), β-caryolanol (5), phytol (6), biochanin A (7), chrysoeriol (8), tanoside II (9) and astragalin (10) by analysis of NMR and MS spectral data.…”
Section: Introductionmentioning
confidence: 99%